CE: Inside an Ebola Treatment Unit. (December 2015) - Wilson, Deborah
Abstract : In December 2013, the first cases of the most recent outbreak of Ebola virus disease (formerly known as Ebola hemorrhagic fever) emerged in the West African nation of Guinea. Within months the disease had spread to the neighboring countries of Liberia and Sierra Leone. The international humanitarian aid organization Médecins Sans Frontières (MSF; known in English as Doctors Without Borders) soon responded by sending staff to set up treatment centers and outreach triage teams in all three countries. In August 2014, the World Health Organization declared the outbreak an international public health emergency. In September 2014, the author was sent by MSF to work as a nurse in an Ebola treatment unit in Liberia for five weeks. This article describes her experiences there. It provides some background, outlines the practices and teams involved, and aims to convey a sense of what it's like to work during an Ebola outbreak and to put a human face on this devastating epidemic. Abstract : The author shares her experiences working in an Ebola treatment unit during a 2014 trip to Liberia with Médecins Sans Frontiéres (Doctors Without Borders), and describes the practices used to combat the epidemic as well as the many challenges the health care teams faced.